Genetic diversity and relationship of indigenous goats of sub-saharan Africa using microsatellite DNA markers. - Muema, E.K. (University of Nairobi, 2006)
This study was undertaken to determine the genetic structure, relationship and genetic diversity among 18 populations of goats from sub-Saharan Africa including Uganda (4), Tanzania (5), Kenya (2), Mozambique (2), Nigeria (3), Mali (1) and Guinea Bissau (1) using 11 microsatellite markers. Heterozygosities, estimates of gene differentiation (FST), genetic distances, multivariate and diversity analyses were performed. Expected heterozygosity ranged from 0.450 in Guinea Bissau to 0.541 in Mbeya, while the observed heterozygosity ranged from 0.441 in Pafuri to 0.560 in the Sebei. Total genetic variability of 5.3% was attributed to differences among populations while 94.7% was attributed to differences within populations. The genetic diversity was low with a mean number of alleles (MNA) per population ranging from 3.82 to 5.91. The analysis of molecular variance (AMOV A) indicated that a greater proportion of the genetic diversity in the sub-Saharan goat populations is within the populations. The genetic distances between sub-Saharan goat populations were generally low. The classification of the sub- Saharan goat populations based on the morphological features (phenotypic characterization) does not concur with the genetic classification revealed in this study. However, theresults confirm earlier studies that the genetic relationships of these populations are much linked to geographical location than the classification based on the size and shape of the horns and ears. It appears likely that the sub-Saharan goats have a common origin and that there is extensive gene flow between populations.